(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
India has recently focused on women’s political participation for gender equality and democracy. Patriarchy upholds a biassed perspective on the role of women in society. These roles have been possible due to the evolution of the binary discourse of the public (for men) & private (for women) realms, with the latter ostensibly relegating women to the house. Near the end of the twentieth century, democratic movements all around the world gained steam, and globalisation sped up. Consequently, women’s movements to dismantle patriarchy through increased representation in political decision-making accelerated. Women’s political engagement is on the rise worldwide, the rate & quality of this development differ between nations. The purpose of this study is to explain why women’s political responsibilities & involvement are typically undervalued compared to men’s, even though women encounter few legal barriers to participating at all levels of political processes. This study uses the development of three structural categories to answer the issue of how patriarchy actually hinders women’s involvement in politics.